Surjective Monotone Mappings on Product Spaces - Bhatt, Biseswar Prashad; Tamang, Badri (Interdisciplinary Journal of Management and Social Sciences, 2025)
The role of duality mappings on the surjectivity of monotone mapping is very crucial. In this paper we study some well-known results on the surjectivity of monotone mappings on reflexive Banach spaces by Browder and its consequences.